A companion to the Holocaust - Gigliotti, Simone 1973- HerausgeberIn; Earl, Hilary Camille 1963- HerausgeberIn (Blackwell companions to world history, 2020)
Part 1: New Orientations and Topical Integrations -- Framing chapter: Devin O. Pendas, 'Final Solution', Holocaust, Shoah, or Genocide? From Separate to Integrated Histories -- Cathie Carmichael, Raphael Lemkin and Genocide before the Holocaust: ethnic and religious minorities under attack -- Dan Stone, Ideologies of Race: the Construction and Suppression of Otherness in Nazi Germany -- William J. Spurlin, Queering Holocaust Studies: New Frameworks for Understanding Nazi Homophobia and the Politics of Sexuality under National Socialism -- Daniel Blatman, Holocaust as Genocide: Milestones in the Historiographical Discourse -- Part 2: Plunder, Extermination, and Prosecution -- Framing chapter: Edward B. Westermann, Old Nazis, Ordinary Men, and New Killers: Synthetic and Divergent Histories of Perpetrators -- Mark Spoerer, The Nazi War Economy, the Forced Labour System, and the Murder of Jewish and Non-Jewish Workers -- Waitman Wade Beorn, All the Other Neighbors: Communal Genocide in Eastern Europe -- Kim Christian Priemel, War Crimes Trials, the Holocaust and Historiography, 1943- -- Bianca Gaudenzi, Crimes against Culture: From Plunder to postwar Restitution Politics -- Part 3: Reframing Jewish Histories -- Framing chapter: Dan Michman, Characteristics of Holocaust Historiography and their Contexts since 1990: Emphases, Perceptions, Developments, Debates -- David Engel, A Sustained Civilian Struggle: Rethinking Jewish Responses to the Nazi regime -- Guy Miron, Ghettos and Ghettoization: History and Historiography -- Martin C. Dean, Survivors of the Holocaust within the Nazi Universe of Camps -- Natalia Aleksiun, Social Networks of Support: Trajectories of Escape, Rescue, and Survival -- Joanna B. Michlic, A Young Person's War: the Disrupted Lives of Children and Youth -- Elisabeth Gallas and Laura Jockusch, Anything But Silent: Jewish Responses to the Holocaust in the Aftermath of World War II -- Part 4: Local, mobile and transnational Holocausts -- Framing chapter: Tim Cole, Geographies of the Holocaust -- Gerhard L. Weinberg, The Global 'Final Solution' and Nazi Imperialism -- Susanne Heim, Refugees' Routes: Emigration, Resettlement, andTransmigration -- David A. Messenger, The Geo-politics of Neutrality: Diplomacy, Refuge and Rescue during the Holocaust -- Alejandro Baer and Pedro Correa, Spain and the Holocaust: Contested Past, Contested Present -- Esther Webman, Contesting the "Zionist" Narrative: Arab Responses to the Holocaust -- Aomar Boum, Re-drawing Holocaust Geographies: A Cartography of Vichy and Nazi Reach into North Africa -- Part 5: Witnessing in dialogue: testifiers, readers and viewers -- Framing chapter: Alan Rosen, The Holocaust Witness: Wartime and Postwar Voices -- Monika J. Flaschka, Sexual Violence: Recovering a Suppressed History -- Jonathan Druker, Ethical Grey Zones: On Coercion and Complicity in the Concentration Camp and Beyond -- Carol Zemel, Holocaust Photography and the Challenge of the Visual -- Nicholas Chare, Holocaust Memory in a Post-Survivor World: Bearing Lasting Witness -- Noah Shenker, Post Memory: Digital Testimony and the Future of Witnessing -- Part 6: Human rights and visual culture -- Framing chapter: Valerie Hébert, The Problem of Human Rights after the Holocaust -- David B. MacDonald, Indigenous Genocide and Perceptions of the Holocaust in Canada -- Avril Alba, Lessons from History? The Future of Holocaust Education -- Amanda F. Grzyb, The Changing Landscape of Holocaust Memorialization in Poland -- Meghan Lundrigan, #Holocaust #Auschwitz: Performing Holocaust Memory on Social Media -- Daniel H. Magilow, Contemporary Holocaust Film Beyond MimeticImperatives.